Length and Duration of Online Discourse Based on Multidisciplinary Analysis of the Student Forum of Media Studies and Social Communication - Postawa Andrzej (Studies in Logic, Grammar and Rhetoric)
The aim of this paper is to investigate the causes influencing the length and duration of online media discourse, which may also mean its “quality” or a kind of “attractiveness”. This goal sets out the issues and basic research questions related to these causes. What causes some discourses take a long time and others end as soon as they begin? What makes one discourse attract the attention of other participants in the discussion, and what causes less interest in the proposed topics? In order to obtain answers to the above questions we study the structure of the text, stylistics, topics of discourses and social interaction of forum participants.